Model Matematika Sederhana Pada Pemanfaatan Bayam Brazil Menggunakan Eco Enzyme Pada Lahan Pekarangan Masyarakat Desa Pulau Semambu - Fitri Maya Puspita; Sisca Octarina; Evi Yuliza; Laila Hanum; Robeah Aryani; Yulia Anisawati (Jurnal Gema Ngabdi, 2023)
Along with the Covid-19 outbreak around the beginning of 2020, the yard is increasingly being used by the Indonesian people. Availability of land determines which commodity crops are suitable for cultivation. The wider the yard, the more variety of plants that can be planted on the land. So it is hoped that there will be a synergy from planting, with the dosage of fertilizer use, maintenance schedules until the harvest is produced according to the target with a systematic mathematical model. The selected plant is Brazilian Spinach. The choice of fertilizers and pesticides in this activity is eco enzyme, liquids that are not only useful as fertilizers and pesticides, but can also be applied in everyday life. Eco Enzyme (EE) or garbage enzyme is a liquid fermented by organic waste. EE's functions include cleaning floors, cleaning vegetables and fruit, repelling insects and cultivating plants. With that in mind, a community service program was held in the form of mentoring for Brazilian spinach cultivation that utilizes EE techniques and management with the concept of a mathematical model